On practice of application of financial and logistic analysis at a modern enterprise - T. V. Shmulevich; N. N. Golivtsova (Путеводитель предпринимателя, 2020)
The article substantiates the need for a detailed analysis of the financial aspects of the logistics activities of domestic companies. A detailed study of enterprise accounts receivable management is presented. A methodological approach to improving the enterprise credit policy is proposed.